Implementation Effectiveness of Electronic Liability Registration - Endah Subekti Tri Astuti; Widayati Widayati (Sultan Agung Notary Law Review, 2021)
The purpose of this study is to determine and analyze: 1) the effectiveness of the current electronic mortgage registration implementation. 2) Factors that affect the effectiveness of the current implementation of electronic mortgage registration. The approach method used in discussing this research problem is a normative juridical approach.The research specification used is descriptive analytical research. This type of data uses secondary data. The data analysis method used in this research is qualitative data analysis. The results of the study concluded: 1) The implementation of HT registration with the HT-el System at the Land Office has not all been carried out in accordance with the procedures stated in the Technical Guidelines for HT-el. Procedural discrepancies, for example, were found in files that were suspended and closed in 2019 until May 12, 2020. Application files that did not comply with the procedures were discovered based on the results of the Land Office inspection, if not checked, the HT-el certificate would be issued automatically on the seventh day. Issuance without any inspection from the Land Office if there is a procedural error, it is feared that it will become a problem in the future. Obstacles in HT registration with the HT-el System occur in PPAT, Banks as creditors and the Land Office. These obstacles arise during the HT registration process, both technically and non-technically. 2). Barriers related to technical aspects include the lack of facilities such as ranking selection, selecting more than one certificate and providing facilities for checking certificate data in HT-el applications. Meanwhile, in non-technical barriers, there are regulations in Permen ATR/BPN No. 5 of 2020 which is not in accordance with UUHT as the legal basis for the Ministerial Regulation issued, where in UUHT the second sheet of APHT and other warrants are submitted to the Land Office in physical form but in Permen ATR/BPN No. 5 of 2020 only in digital form of scan results.